POLA KOMUNIKASI USTADZAH DAN SANTRI DALAM MENYAMPAIKAN METODE QIROATI TPQ AR-RIFAI JEMBER - Ani Roudatul Jannah; M.H. Thamrin (MEDIAKOM, 2023)
This study aims to analyze the communication patterns used by Ustadzah towards students in delivering the Qiroati method. The Qiroati method is an approach to learning tajweed through good and correct recitation of the Qur'an. Where the discussion focuses on three main aspects. First, the interactional style used by Ustadzah to explain the concept of the Qiroati method to students. Second, the communication relationship between the Head of TPQ and Ustadzah in order to improve the ability to read the students' Al-Qur'an. Third, what factors influence Ustadzah in conveying the Qiroati method to students. The use of instructional communication theory provides a relevant framework, this is in line with the researcher's aim to analyze how the communication patterns of Ustadzah and students, especially in learning the Qiroati method. This research uses descriptive qualitative methods described through classroom observations, in-depth interviews with Ustadzah and students, and document analysis to find out the communication strategies applied by Ustadzah in teaching the Qiroati method. The technique of collecting data sources uses purposive sampling method to determine the criteria of the informants, the selection of samples based on the criteria of Ustadzah who have been teaching from a period of 2.5-6 years with a total of 5 informants, while for santri, namely those who can answer questions from researchers, with ages 10-12 years with a total of 6 santri. The use of two-way interaction in the interaction of Ustadzah and santri contributes to the learning environment, in this case both play an active role in the interaction. Ustadzah's clear language when presenting the material also affects the understanding of students, especially regarding the Qiroati method, not only that, a good communication relationship between Ustadzah and the Head of TPQ affects the success of students in reading the Qur'an. The results of interviews with Ustadzah, students, and the Head of TPQ show that the communication patterns that occur in the learning environment are going well, from Ustadzah to the Head of TPQ have practiced the right communication patterns so that students understand the material that has been delivered.